The economics of money, banking and financial markets - Mishkin, Frederic S. (HarperCollins, 1994)
This book covers issues such as the growing internationalization of financial markets. It discusses topics such as problems of financial intermediation in the countries of Eastern Europe and the former Soviet Union; basic puzzles of financial structure throughout the world; international banking; the globalization of financial futures markets, Japanese, and German banking arrangements; problems in the banking industry outside of the United States; the woes of Lloyd's of London; a comparison of central bank independence and macroeconomic performance in 17 countries; the conduct of monetary policy in other countries, and the September 1992 foreign exchange rate crisis. The book also deals with closely related topics such as how developments in the foreign exchange market and other international financial markets affect the U.S. economy and the conduct of monetary policy.